A Critical View of Laws and Regulations of Artificial Intelligence in India and China - Dadhich, Avinash (Kathmandu School of Law Review, 2018)
This research paper deals with the general understanding of AI technology and its laws and regulations in India and China. It examines this issue from developing countries perspective and focusing on India and China, as they represent around 40 % of the global population and are in the top 3 economies in the 21st century. Their experiences and approach may be useful for other developing and least developing counties due to similarities in socio-economic conditions e.g. food, poverty, employment and education etc. It is relevant to mention that India and China share many common grounds (high population and GDP growth etc.), but there are few important factors like democracy, demographic situation, the difference in economic power etc., make it an interesting case for other developing counties to choose their path. AI is considered the most revolutionary technology after electricity and designing a robust legal and regulatory mechanism is a challenging task at national and international level. This paper argues that such regulations should be guided by technological and socio-economic requirements of a country. Developing and developed world have different opportunities and challenges from AI, however, a general AI may create challenges before the existence of human civilization and raises many moral, ethical and legal questions; therefore, it is suggested to develop a well thought and holistic regulatory mechanism (laws and institutions) at national and international level.DOI: https://doi.org/10.46985/jms.v6i2.202